Health behaviors and subsequent mental health problems during the COVID-19 pandemic: A longitudinal analysis of adults in the UK - Russell Jonsson, Kenisha; Taylor-Robinson, David C.; Schultz Straatmann, Viviane; Melis, Gabriella; Adjei, Nicholas Kofi (Frontiers in Public Health, 2023)
Public health mitigation policies aimed at slowing the spread of COVID-19 led to an increase in mental health problems (MHPs). This study examines the association between multiple pre-pandemic health behaviours and MHPs prior to, and during, the COVID-19 pandemic. We analysed a representative population sample of 11,256 adults (aged 20-65 years) from Understanding Society – The UK Household Longitudinal Study. Baseline data from participants interviewed in 2017/2019 (wave 9) were linked to web surveys conducted during the COVID-19 pandemic. We used latent class analysis (LCA) to identify mutually exclusive health behaviour (physical activity, alcohol consumption, eating habits and smoking tobacco) clusters by gender, and examined the sociodemographic correlates of each cluster. We assessed how pre-pandemic latent classes of health behaviours were associated with changes in MHPs during the pandemic using fixed effects regression models. Three health behaviour clusters were identified: positive (33 %), moderate (24%) and high risk (43%), where similar behaviours clustered within individuals and sociodemographic circumstances. In particular, gender, age, migrant status and ethnicity were found to have strong associations with each cluster. Our results also demonstrated a clear association in MHPs with health behaviours both prior to, and during the pandemic. There were significant increases in MHPs between 2017/2019 and January 2021, with fluctuations coinciding with changes in public health mitigation policies. Assessments across the three clusters showed about 25.2%, 16.9% and 0.7% increases in MHPs in the positive, moderate and high risk health behaviour clusters respectively. This study shows that pre-pandemic health behaviours were significantly associated with mental health before and during the pandemic. Holistic policy interventions and promotions targeting multiple health behaviours may be an effective strategy to improve mental health in the pandemic recovery period.